Interactive Effects of Ammonia and Light Intensity on Ocular, Fear and Leg Health in Broiler Chickens - Miller, W.W.; Maslin, W.R.; Thaxton, J.P.; Olanrewaju, H.A.; Dozier, W.A.; Purswell, J.; Branton, S.L. (International Journal of Poultry Science, 2007)
High atmospheric ammonia is detrimental to poultry health under confined environments, especially in its inducement of eye lesions in juvenile chicks during the first week of grow-out. Furthermore, welfare consultants have expressed concerns that low light-intensity may cause damage to the eye lens or lead to blindness. The objective of the present study was to evaluate the interactive effects of ammonia and light-intensity on ocular, fear and leg health in broiler chickens. The interactive effects of inhalation of ambient air with elevated ammonia concentrations and differing light-intensities on eye lesions and welfare (fear and leg-health) in male and female broiler chickens under environmentally controlled conditions were evaluated. Results indicated that ammonia concentrations at 25 and 50 ppm induced eye lesions after day 7 of initial exposure. Light-intensity alone yielded no significant eye lesions. However, light-intensity of 0.2 and 20 lx for 14 days further exacerbated eye lesions. Nevertheless, the effect of ammonia was more pronounced than that of light-intensity. These conditions worsened as duration of ammonia concentration exposure and light-intensity increased during the 7 days of exposure. Eye lesions induced by the interaction of ammonia and light intensity decreased significantly beginning one week after cessation of ammonia exposure, such that the apparent effects were no longer evident. The findings in this investigation suggest that ammonia induced uveitis in chickens clears rapidly upon cessation of ammonia exposure and that fear along with leg health were not significantly affected by ammonia, light-intensity or their interaction. This suggests that elevated ammonia levels in air and low light intensity did not induce stress in broiler chickens.